Chapter Il 'brutto anatroccolo' dell'istruzione e formazione professionale. Genetica di una pretesa ma insostenibile 'inferiorità' - Bertagna, Giuseppe (Studies on Adult Learning and Education, 2022)
The separative logic is not educational. The essay reviews the historical events that have generated an undervaluation of vocational training pathways compared to education pathways. This "minority" of perception and legislation stems from a logic of separation with many faces which, taken all together, with etiological spirit and historical-ordinamental contextualization, explain the "untenable" inferiority of vocational education: people (the 'inferiors') and political-bureaucratic elite (the 'superiors'), nature and culture, man and citizen, etc. These separations concerned the idea of labor (one among them, the opposition between 'manual labor' and 'intellectual labor') and did not allow for increasing the educational power of it. Only a logic of integration (embedded and embodied) can defuse the ideas of separation and provide an organic and holistic image of education.